In praise of ethnography: towards a rich understanding of crime and deviance - Müller, Thaddeus (Kriminologisches Journal, 2013)
In this article I show how ethnography can be used to get a rich understanding of crime and deviance. I will highlight the advantages of ethnography for criminology by referring to the work of others and by using detailed examples of the ‘back-stage’ experience of my own fieldwork among the soccer-hooligans of Ajax, Amsterdam. This means that my research experience is not rewritten to fit the ideal front-stage of the supposedly “objective” researcher; but instead that this article explicitly describes the embodied, emotional and personal experiences of doing ethnography. Here I will show that the advantages of ethnography for criminology are inherently related to several qualities of this methodological approach: 1. continued physical access, 2. unanticipated situations, 3. thick contextual information, 4. natural triangulation and 5. the embodied research-experience.